A qualitative study on antibiotic use and animal health management in smallholder dairy farms of four regions of India. Issue 1 (1st January 2020) - Sharma, Garima; Mutua, Florence; Deka, Ram Pratim; Shome, Rajeshwari; Bandyopadhyay, Samiran; Shome, BR; Goyal Kumar, Naresh; Grace, Delia; Dey, Tushar Kumar; Venugopal, Nimita; Sahay, Swati; Lindahl, Johanna
ABSTRACT: Background: Antimicrobial resistance (AMR) is a major global public health issue. In India, access to medicines is poorly regulated and therefore antibiotics in dairy cattle are commonly used by farmers without consulting with veterinarians. This study was conducted to understand practices and knowledge related to antibiotic use and AMR among dairy farmers and veterinary professionals in selected urban and peri-urban areas of India. Methods: A total of 28 focus group discussions with farmers and 53 interviews with veterinary professionals were carried out. Results: Mastitiswas identified as the main animal health challenge. Antibiotic consultation behavior of farmers depended on the availability of veterinarians. Except in Bangalore, farmers were found to often treat animals on their own. They were found unaware of the concept of AMR, but knew the importance of vaccination. Veterinarians included in the study had a good understanding of antibiotics, AMR, and zoonotic diseases. Conclusion: The knowledge level and practices observed in the study related to the use/abuse of antibiotics can potentially increase the risk of development of AMR and its transfer in the community. Our findings can help support AMR – mitigation efforts in the country, including the design of better policies on antibiotic use in dairy.